Working With Plantation Communities: A Reflection of Social Issues - Abdul Rahman Saili Jamayah Sail (Universitas Ahmad Dahlan, 2013)
AbstractThe plantation industry in Malaysia is aggressively expanding over the past decade driven by global demands for palm oil as a food staple and more recently bio fuels. The rapid growth in the industry is heavily dependent upon high labour and workforce. Such intensity has carried out social impact on the communities including plantation workers, small holders and their dependents. Therefore, this paper will outline what appear to be never ending issues impetus social problems. Ethnic conflict, fighting, gambling, alcohol abuses areonlya few issues that call for immediate multi-action plan from all involved stakeholders. Those issues can be the causes as well as the effects. The contributing factors form a chain reaction to the whole social dynamics in the plantationâ€™s climate.The main aim is hence to breach the gap between industries, practitioners, and academicians in order to develop the competencies of the next generation social workers. They can play their roles in tackling the social issues, taking into account the different contexts and environment.Â Â Keywords: Social issues, Plantations, Estate communities, Cause and Effect